1989
DOI: 10.3109/10715768909087937
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation and Oxidative Stress

Abstract: Antioxidants such as mannitol, butylated hydroxytoluene and alpha-tocopherol enhance the growth of polyoma virus transformed and non-transformed BHK-21 cells. In the case of mannitol this is observed even in the absence of added calf serum. In part these effects may operate to protect cellular growth control mechanisms. On the other hand oxidants such as H2O2 and t-butyl hydroperoxide can inhibit growth and overall cellular protein synthesis, through mechanisms that are likely to involve radicals. In the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 14 publications
3
45
0
1
Order By: Relevance
“…This supports the notion of a prooxidant tumor environment arising during tumor formation [13,14]. Yet, contrary to our hypothesis, which sought to evaluate whether a greater oxidative response correlated with a progressively enlarging tumor, we interestingly observed a greater extent of oxidation stress during the early time intervals than the 6-week time-point.…”
Section: Discussionsupporting
confidence: 63%
“…This supports the notion of a prooxidant tumor environment arising during tumor formation [13,14]. Yet, contrary to our hypothesis, which sought to evaluate whether a greater oxidative response correlated with a progressively enlarging tumor, we interestingly observed a greater extent of oxidation stress during the early time intervals than the 6-week time-point.…”
Section: Discussionsupporting
confidence: 63%
“…In recent years, several studies suggest metabolic production of ROS is tightly regulated and serves a physiological function during mitogenic stimulation of cultured cells (6 -11). It has been suggested that ROS operate as a key signaling process in the cascade of events leading to cell proliferation following stimulation with platelet-derived growth factor (9), epidermal growth factor (10), cytokines and antigen receptors (11), and oncogenic Ras (12). Although these studies provide evidence for a possible role of redox signaling during cellular proliferation, it is currently unknown whether antioxidant enzymes regulate progression through the cell cycle.…”
mentioning
confidence: 88%
“…(92,93), whereas higher concentrations cause a reduction in cell growth and eventually cell death. The growth promoting properties of O 2 -· at low concentrations, and cytotoxic properties at high concentrations, are illustrated in Figure 1.…”
Section: Reactive Oxygen Species As Signaling Moleculesmentioning
confidence: 99%